PAINTING MENTIONS IN ANCIENT INDIAN TEXTS: प्राचीन भारतीय ग्रन्थ में चित्रकला उल्लेख - Mahore, Nisha (International Journal of Research -GRANTHAALAYAH, 2019)
Engish : In ancient Indian texts, the rules related to painting are mentioned in detail, in which texts of poetry, drama, epic, Puranas, Upanishads and various disciplines describe their popularity in ancient tradition and cultural methods of Indian painting and public opinion. Apart from this, there are some texts in which free and comprehensive painting has been explained in detail. For example, there are 269 chapters in this book composed by Vishnudharmottara Purana Markandeya. Under which, in the third section, Sanskrit subjects are especially important for the fine arts. In which chapters 1 to 118 are told about art. In this book, nine chapters from 35 to 43 are of Chitrasutra. It is very popular and most notable and well-known. In which detailed information related to the painting is given, which is not found in any other book before it. In the same way, in the epic, Ramayana, Mahabharata, there is a description of paintings on chitrashalas, palaces, chariots and the great dramatist Bhasa has described the paintings in his three plays Swapnavasavadattam, Pratigya Yogandharayana and Dutavakya. Apart from this, painting has also been mentioned in texts like Abhilachirtartha Chintamani, Mansar, Samranga Sutradhar. It is only through these ancient Indian texts that the painter has been able to study the artifacts microscopically. That is, following the rules related to the picture in these texts can be seen in miniature paintings of Ajanta, Mughal, Rajasthan. By following these rules, painters have been able to express their artistry by imbibing expressions like harmony, balance and cooperation, effectiveness in their artworks. The example of which can be seen in the artwork made by Bengal school and artists of Calcutta. Hindi : प्राचीन भारतीय ग्रन्थों में चित्रकला से सम्बन्धित नियमों का उल्लेख विस्तृत रूप से मिलता है जिसमें काव्य, नाटक, महाकाव्य, पुराण, उपनिषद्‌ व विभिन्न विषयों के ग्रन्थों द्वारा भारतीय चित्र लेखन की प्राचीन परम्परा व सांस्कृतिक विधियों एवं जनमानस में उनकी लोकप्रियता का वर्णन मिलता है। इसके अतिरिक्त कुछ ऐसे ग्रन्थ भी हैं, जिनमें स्वतन्त्र व व्यापक रूप से चित्रकला की व्याख्या विस्तार रूप से की गयी है। उदाहरण स्वरूप विष्णुधर्मोत्तर पुराण मार्कण्डेय द्वारा रचित इस ग्रन्थ में 269 अध्याय हैं। जिसके अन्तर्गत तीसरे खण्ड में संस्कृत विषयों में विशेषकर ललित कलाओं के लिये सर्वाधिक महत्वपूर्ण हैं। जिसमें अध्याय 1 से लेकर 118 तक कला के बारे में बताया गया है। इसी ग्रन्थ में 35 से 43 तक नौ अध्याय चित्रसूत्र के हैं। यह बहुत चर्चित व सर्वाधिक उल्लेखनीय एवं बहुचर्चित हैं। जिसमें चित्रकला से सम्बन्धित विस्तृत जानकारी दी गयी है, जो इससे पहले अन्य किसी ग्रन्थ में नहीं मिलती। इसी तरह से महाकाव्य, रामायण, महाभारत में चित्रशालाओं, महलों, रथों पर चित्रकारी का वर्णन मिलता है व महान नाटकार भास ने अपने तीन नाटकों स्वप्नवासवदत्तम्‌, प्रतिज्ञा योगंधरायण तथा दूतवाक्य में चित्रों के बारे में बताया है। इसके अलावा अभिलषितार्थ चिन्तामणि, मानसार, समरांगण सूत्रधार जैसे ग्रन्थों में भी चित्रकला का उल्लेख किया गया है। इन प्राचीन भारतीय ग्रन्थों के माध्यम से ही आज चित्रकार कलाकृतियों का अध्ययन सूक्ष्मरूप से करने में सक्षम हो सका है। अर्थात्‌ इन ग्रन्थों में चित्र से सम्बन्धित नियमों का पालन अजन्ता, मुगल, राजस्थान के लघु चित्रों में देखा जा सकता है। इन नियमों का पालन करते हुये ही चित्रकार अपनी कलाकृतियों में सामंजस्य, सन्तुलन व सहयोग, प्रभाविता जैसे भावों को आत्मसात करते हुये अपनी कलाकृति को अभिव्यक्त कर पाने में समर्थ हो सके हैं। जिसका उदाहरण बंगाल स्कूल व कलकत्ता के कलाकारों द्वारा बनायी कलाकृतियों में देखा जा सकता है।